Symbol of Women's Struggle through the Character Sur in the Film Copying Light by Wregas Bhanuteja: Semiotic Analysis - Leony Indra Farera Achmad; Resdianto Permata Raharjo (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze the signified, the signifier, and the meaning generated from their relationship in representing the symbol of women's struggle in the character Sur in the film Penyalin Cahaya. The population in this study is all scenes in the film Penyalin Cahaya, while the research sample consists of scenes containing elements of signs relevant to women's struggles. The research instrument used is the researcher herself as the main instrument, with the aid of a data analysis table to systematically classify the signifiers and signifieds. The data collection technique was carried out through repeated observations of the film, while the data analysis tool used Ferdinand de Saussure's semiotic approach with descriptive qualitative methods. Data validity was strengthened through time triangulation techniques. The results show that the signifiers in the film are manifested through various visual and narrative elements, such as lighting, color, and certain symbols that appear in the scenes. Meanwhile, the signifiers represent various forms of women's struggles, such as resistance to injustice, social pressure, trauma, and efforts to obtain justice. The relationship between the signifier and the signified produces the meaning of the symbol of women's struggle as a form of resistance to a patriarchal system and a culture that tends to blame the victim. Thus, this film not only functions as a medium of entertainment, but also as a means of social criticism of the reality of gender inequality in society.